1193. Human Transcriptomic Analysis of Periprosthetic Joint Infection. (31st December 2020) - Masters, Thao; Bhagwate, Aditya; Dehankar, Mrunal; Greenwood-Quaintance, Kerryl; Abdel, Matthew P; Patel, Robin; Patel, Robin
Abstract: Background: Periprosthetic joint infection (PJI), a devastating complication of total joint replacement, is of incompletely understood pathogenesis and may sometimes be challenging to clinically distinguish from other causes of arthroplasty failure. Methods: We characterized human gene expression in 93 specimens derived from surfaces of resected arthroplasties, comparing transcriptomes of subjects with infection- versus non-infection-associated arthroplasty failure. Results: Differential gene expression analysis confirmed the association of 28 previously investigated biomarkers with PJI- bactericidal/permeability increasing protein (BPI), cathelicidin antimicrobial peptide (CAMP), chemokines CCL3, CCL4, and CXCL2, colony stimulating factor 2 receptor (CSF2RB), colony stimulating factor 3 (CSF3), alpha-defensin (DEFA4), receptor CD64B, intercellular adhesion molecule 1 (ICAM1), IFNG, IL13RA2, IL17D, IL1A, IL1B, IL1RN, IL2RA, IL2RG, IL5RA, IL6, IL8, lipopolysaccharide binding protein (LBP), lipocalin (LCN2), lactate dehydrogenase C (LDHC), lactotransferrin (LTF), matrix metallopeptidase 3 (MMP3), peptidase inhibitor 3 (PI3), and vascular endothelial growth factor A (VEGFA), as well as identified three novel molecules with diagnostic potential for detection of PJI- chemokine CCL20, coagulation factor VII (F7), B cell receptor FCRL4. Comparative analysis of infections caused by staphylococcal versus non- staphylococcal and Staphylococcus aureus versus Staphylococcus epidermidis showed significant elevated expression of IL13, IL17D, and metalloprotease protein MMP3 in staphylocococcal infections, and increased expression of IL1B, IL8, and platelet factor PF4V1 in S. aureus infections. Pathway analysis of over-presented genes suggested activation of host immune response and cellular maintenance and repair functions in response to invasion of infectious agents. Conclusion: Our study provides new potential targets for diagnosis of PJI and targets for differentiation of PJI-associated infectious agents. Disclosures: Matthew P. Abdel, MD, Dr. Abdel receives royalties from Stryker on certain hip and knee products, and is a paid consultant for Stryker. (Consultant) Robin Patel, MD, Accelerate Diagnostics (Grant/Research Support)CD Diagnostics (Grant/Research Support)Contrafect (Grant/Research Support)Curetis (Consultant)GenMark Diagnostics (Consultant)Heraeus Medical (Consultant)Hutchison Biofilm Medical Solutions (Grant/Research Support)Merck (Grant/Research Support)Next Gen Diagnostics (Consultant)PathoQuest (Consultant)Qvella (Consultant)Samsung (Other Financial or Material Support, Dr. Patel has a patent on Bordetella pertussis/parapertussis PCR issued, a patent on a device/method for sonication with royalties paid by Samsung to Mayo Clinic, and a patent on an anti-biofilm substance issued.)Selux Dx (Consultant)Shionogi (Grant/Research Support)Specific Technologies (Consultant)